Constraints encountered by the fish farmers while adopting indigenous practices - Biswarup Saha; Rajita Devi (Journal of Traditional and Folk Practices (JTFP), 2016)
Field survey was carried out in the Nagaon district of central Assam to identify the constraints faced by the indigenous fish farmers while adopting indigenous technical knowledge in fisheries. The present study identified and ranked nine constraints as perceived by the indigenous fish farmers and documented three popular suggestions perceived by them to overcome the constraints to save and conserve the Indigenous Traditional Knowledge (ITK) for wider application in fisheries based on the information gathered through usage of semi structured interview schedule, focus group discussion and observation methods. All the farmers perceived that ‘ITK alone is not complete panacea for fish production practices’. Around 77.50% of the farmers were having lack of full confidence in applying ITKs as Government officials and educated people give less recognition to this knowledge. All the respondents (100%) suggested that Government officials should look at the traditional knowledge with due consideration and be ready for its proper assessment. The farmers practicing ITKs should be made partners with research scientists for evolving appropriate technologies. Local ITK practitioners are needed to be honoured and recognized.